2018
DOI: 10.1051/matecconf/201814901023
|View full text |Cite
|
Sign up to set email alerts
|

The benefic effect of Moroccan oil shale’s ash on blended cement (CMII)

Abstract: Recycling of Tarfaya’s oil shales (OSA) was conducted for two essential reasons: First, to follow the change of their mineralogical composition with the heat treatment and second to investigate the possibility of their use in building materials. The mineral compositions and the mineralogical transformations of the oil shale during their thermal treatment were followed respectively by X-ray fluorescence (XRF), by X-ray diffraction analysis (XRD) and Fourier transform infrared (FTIR). The XRF showed that the min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…The amount of mayenite increases with rising ashing temperatures, reaching more than 11 wt.% at 900 °C. The presence of mayenite in Ca-rich ashes has also been reported in some of the literature [58][59][60]. The complete results of the XRD analysis of the ashes are presented in Tables A3 and A4.…”
Section: Mineral Phase Characterisation and Predictionsupporting
confidence: 70%
See 1 more Smart Citation
“…The amount of mayenite increases with rising ashing temperatures, reaching more than 11 wt.% at 900 °C. The presence of mayenite in Ca-rich ashes has also been reported in some of the literature [58][59][60]. The complete results of the XRD analysis of the ashes are presented in Tables A3 and A4.…”
Section: Mineral Phase Characterisation and Predictionsupporting
confidence: 70%
“…Moreover, a fair amount of mayenite (Ca 12 Al 14 O 33 ) is present in F ashes, which is formed by the interaction between CaO and Al 2 O 3 . The amount of mayenite increases with rising ashing temperatures, reaching more than 11 wt.% at 900 • C. The presence of mayenite in Ca-rich ashes has also been reported in some of the literature [58][59][60]. The complete results of the XRD analysis of the ashes are presented in Tables A3 and A4.…”
Section: Mineral Phase Characterisation and Predictionsupporting
confidence: 63%
“…It is suggested that the first event of mass loss (at up to 300 °C) is attributed to the decomposition of the calcium phosphate compounds. The second mass loss in the range of 650–800 °C is attributed to the pyrolysis residues of organic matter and/or the decomposition of carbonate minerals . In addition, in the second process of mass loss, the mass loss decreases as the pH becomes more acidic.…”
Section: Resultsmentioning
confidence: 99%
“…The second mass loss in the range of 650–800 °C is attributed to the pyrolysis residues of organic matter and/or the decomposition of carbonate minerals. 25 In addition, in the second process of mass loss, the mass loss decreases as the pH becomes more acidic. The fact that the amount of calcite (CaCO 3 ) decreases is in agreement with the composition of the mass shown in Table 4 , which shows that the more acidic the pH, the smaller the amount of calcite (CaCO 3 ) in the mixture.…”
Section: Resultsmentioning
confidence: 99%